Dynamic assessment in developing EFL learners’ depth of vocabulary knowledge through critical reading - Sana’ati, Mohammad Kazemian; Khonamri, Fatemeh; Azizi, Mahmoud; Molana, Khazar (Penerbit Universiti Kebangsaan Malaysia, 2019)
The emergence of dynamic assessment (DA) in applied linguistics has opened new horizons in second language acquisition (SLA) and language assessment. This quasi-experimental study determined the effect of DA in fostering Iranian EFL learners’ depth of vocabulary knowledge through critical reading. A total of 61 upper-intermediate EFL learners were selected as participants and were randomly divided into treatment group (DA, n = 31) and control group (non-DA, n = 30). A vocabulary Scholastic Aptitude Test (SAT) was administered non-dynamically to both groups as pre-test. Mediation programs which included Enrichment Program and assessment sessions were held within six weeks. Graduate Prompt Approach was used as a mediation procedure in the DA group. After receiving six mediation sessions, the same test was administered dynamically as a post-test to the DA group and non-dynamically to the non-DA group. One month onward, far transfer assessment test was done via DA procedures to the DA group. The results of independent t-test, one-way ANOVA, and Pearson Correlations indicated that there was a significant difference in scores between the DA and non-DA groups. Findings indicated that the mediation program and DA procedures enriched the students’ depth of vocabulary knowledge. This study suggests that DA procedures can help lackadaisical learners to promote their language competency.